PEMBELAJARAN TEKS KRITIK DAN ESAI PADA SISWA KELAS XII SMA NEGERI 6 PONTIANAK TAHUN PELAJARAN 2019/2020 - Riyan Handari; Christanto Syam; Abdussamad Abdussamad (Universitas Tanjungpura, 2021)
AbstractThis study generally discusses the learning of critical texts and essays for class XIIstudents of SMA Negeri 6 Pontianak in the 2019/2020 academic year. The researchmethod used is descriptive in the form of qualitative research. The source of the datain this research is learning activities facilitated by the Indonesian language teacherClass XII SMAN 6 Pontianak. The data in this study are the implementation plan oflearning, the learning process and the assessment of learning critical texts andessays in Indonesian language learning obtained through observation activities. Thedata collection techniques used by the author in this study are observationaltechniques, and documentation techniques. From the results of the analysis andobservations of researchers, it can be concluded that the learning of Criticism andEssay texts for class VII students of SMA Negeri 6 Pontianak is still not entirely inaccordance with the 2013 curriculum and the syllabus of Indonesian subjects. Basedon this analysis, the teacher should facilitate and present activities for students tocommunicate the knowledge and information they have obtained so that the teacherknows the extent to which students understand the material that has been studied.Keywords: Learning, Criticism, Literature,